A method for preparing ADC12 aluminum alloy by selectively removing silver and retaining aluminum from failed photovoltaic silicon wafers
Patent Information
- Application Number
- CN202611386641.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]但是现有的处理工艺存在金属铝回收率低、酸碱体系同步侵蚀硅基底、银离子易在铝表面置换析出银膜、银脱除不完全、酸药剂消耗量大、废液排放量大等不足
[0025] (1) The method of the present invention uses failed photovoltaic silicon wafers generated during the recycling process in the photovoltaic industry as raw materials, forms a protective film through a pre-passivation liquid, and then selectively dissolves the silver grid with a silver-containing leaching solution to completely retain the aluminum back field, thereby obtaining a silicon-aluminum composite raw material that can directly replace high-purity silicon for the preparation of ADC12 alloy, realizing efficient resource utilization and low-cost recycling of failed photovoltaic silicon wafers.
Smart Images

Figure CN122918368A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photovoltaic solid waste recycling and aluminum alloy preparation technology, and relates to a method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy. Background Technology
[0002] ADC12 aluminum alloy (Al-Si-Cu series aluminum alloy) is widely used in automotive parts, electronic housings, and other fields due to its excellent casting performance, mechanical properties, and cost advantages, resulting in a large market demand. Currently, the mainstream industrial production process for ADC12 aluminum alloy still uses primary industrial high-purity silicon and electrolytic aluminum ingots as raw materials for blending and smelting. This production not only relies on energy-intensive metallurgical silicon resources, resulting in high raw material costs, but also has high carbon emissions and resource consumption during the primary silicon smelting process, making it difficult to align with the current development trend of energy conservation, emission reduction, and solid waste recycling in the non-ferrous metals industry.
[0003] The photovoltaic industry generates a large number of scrapped, damaged, discolored, and faulty silicon wafers. These wafers have a crystalline silicon substrate, contain silver grid lines on the front side, and a continuous aluminum back surface formed by sintering on the back side. They are valuable solid waste composed of silicon, silver, and aluminum. Currently, the recycling of photovoltaic silicon wafers mainly includes the traditional process of removing aluminum first and then removing silver, the process of removing silver and retaining aluminum with nitric acid as a single corrosion inhibitor, and the process of thiourea complexing silver immersion.
[0004] However, existing processing techniques suffer from drawbacks such as low aluminum recovery rates, simultaneous acid-base corrosion of the silicon substrate, easy silver ion displacement and precipitation of silver films on the aluminum surface, incomplete silver removal, high acid reagent consumption, and large wastewater discharge. Furthermore, the industry currently lacks a process for directly using the solid-phase composite material generated after silver removal from failed photovoltaic silicon wafers as raw material to further prepare ADC12 aluminum alloy.
[0005] In summary, there is an urgent need to develop a low-aluminum-loss extraction and recycling process for failed photovoltaic silicon wafers that is compatible with scrap materials, and also suitable for the preparation of ADC12 aluminum alloy. Summary of the Invention
[0006] To address the aforementioned deficiencies in existing technologies, the present invention aims to provide a method for selectively removing silver from failed photovoltaic silicon wafers while preserving aluminum to prepare ADC12 aluminum alloy. This method uses failed photovoltaic silicon wafers generated during the recycling process in the photovoltaic industry as raw materials. A protective film is formed through a pre-passivation solution, and then the silver grid is selectively dissolved with a silver-containing leaching solution while completely preserving the aluminum back field. This yields a silicon-aluminum composite raw material that can directly replace high-purity silicon in the preparation of ADC12 alloy, achieving efficient resource utilization and low-cost recycling of failed photovoltaic silicon wafers.
[0007] To achieve the above-mentioned technical objectives, the present invention provides a method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy. The method involves crushing and screening the failed photovoltaic silicon wafers, immersing them in a pre-passivation solution to form a passivation film, then dissolving and removing silver, and separating the solid and liquid phases to obtain a silver-containing leachate and a silicon-aluminum composite solid phase. The silicon-aluminum composite solid phase is then smelted and cast into ADC12 aluminum alloy by adding raw materials including metallic aluminum according to the composition of the ADC12 aluminum alloy, thereby obtaining an ADC12 aluminum alloy ingot.
[0008] The method of this invention can selectively remove silver from failed photovoltaic silicon wafers while retaining aluminum and silicon components. The principle is as follows: the pre-passivation solution preferentially interacts with the exposed aluminum back surface of the failed photovoltaic silicon wafer, generating a dense and stable aluminum hydroxide passivation film. This effectively isolates the aluminum and silicon substrate from the leaching agent during subsequent leaching, inhibiting the dissolution of aluminum and silicon. The silver grid on the front side of the silicon wafer has low reactivity with the pre-passivation solution, making it difficult to form a complete and robust protective film. Therefore, it can be preferentially oxidized and dissolved during selective silver dissolution and enter the liquid phase. After solid-liquid separation, silver is enriched in the silver-containing leaching solution, facilitating further recovery; while aluminum and silicon are retained in the form of a silicon-aluminum composite solid phase. When this composite solid phase is subsequently smelted with aluminum and other raw materials according to the composition of ADC12 aluminum alloy, the surface passivation film can decompose at high temperature or be removed into the slag phase. Aluminum and silicon elements directly enter the alloy melt, achieving resource utilization of aluminum and silicon while avoiding the adverse effects of impurities such as silver on the microstructure and properties of the ADC12 aluminum alloy.
[0009] As a preferred embodiment, the crushing and screening process controls the particle size to be 2-20 mm; the crushing and screening process also includes a cleaning process. By controlling the particle size within the range selected in this invention, it is beneficial to ensure that the silver grids of the silicon wafer are fully exposed and that the silver immersion solution effectively contacts the silver layer, achieving a high silver dissolution rate, while avoiding damage to the aluminum passivation film and excessive aluminum loss due to excessively fine particles, and simultaneously balancing the passivation failure problem of crushed scraps. The cleaning process removes dust and impurities from the silicon wafer surface, avoiding damage to the pre-passivation film and the silver immersion solution system.
[0010] Furthermore, the cleaning process takes 3 to 8 minutes.
[0011] As a preferred embodiment, the failed photovoltaic silicon wafer mainly contains 92~94wt% Si, 0.6~1.0wt% Ag, and 4~6wt% Al.
[0012] As a preferred embodiment, the pre-passivation solution is a 0.4-0.6 wt% tartaric acid aqueous solution, and the immersion time is 1-3 min. This invention uses a low-concentration tartaric acid aqueous solution to generate a uniform, dense, and stable aluminum hydroxide passivation protective film on the aluminum back surface of the silicon wafer, isolating it from subsequent silver nitric acid immersion solution, inhibiting aluminum corrosion, while not damaging the front silver grid lines or affecting the complete dissolution of silver. Experiments have shown that if the concentration of tartaric acid is too low or the immersion time is too short, it will lead to insufficient complexation oxidation reaction with the aluminum back surface metal, making it difficult to continuously generate a complete aluminum hydroxide passivation film, resulting in poor corrosion resistance. Conversely, if the concentration is too high or the immersion time is too long, the passivation film will become excessively thick and porous, easily detaching, causing silver ion replacement plating and a decrease in silver removal rate.
[0013] As a preferred embodiment, after the soaking is completed, a rinse is performed to remove a large amount of free tartaric acid aqueous solution adhering to the surface of the silicon wafer.
[0014] As a preferred embodiment, the silver removal process employs an anti-corrosion silver immersion solution, which, by mass percentage, comprises the following components: 3-6% nitric acid, 0.8-1.5% tartaric acid, 0.3-0.6% thiomalic acid, 0.15-0.25% ammonium nitrate, 0.1-0.2% fatty alcohol polyoxyethylene ether, and the balance being water. The anti-corrosion silver immersion solution of this invention uses nitric acid as the main silver dissolving agent, providing oxidizing and acidic conditions for rapid dissolution of the silver grid. The higher concentrations of tartaric acid and thiomalic acid constitute a binary composite aluminum corrosion inhibition system, which inhibits aluminum corrosion and prevents silver re-plating by adsorbing and forming a film on the aluminum back surface and complexing silver ions. Simultaneously, a small amount of ammonium nitrate is used to stabilize acidity, buffer pH, and accelerate mass transfer, while the fatty alcohol polyoxyethylene ether is used to reduce surface tension, enhance penetration and wetting of broken silicon wafer fragments, and ensure uniform contact of the solution. In some cases, using too little nitric acid will significantly reduce the dissolution rate of the silver grid, while using too much will destroy the alumina hydroxyl passivation film generated in the pre-passivation process. Excessive nitric acid will also corrode the aluminum back surface, resulting in high aluminum loss. Furthermore, the amount of ammonium nitrate should not be too high, as it will compete with thiomalic acid and tartaric acid for adsorption, weakening the film-forming effect of the organic corrosion inhibitor on the aluminum surface and reducing efficiency.
[0015] Furthermore, the nitric acid is prepared by diluting commercially available 65% industrial concentrated nitric acid with water.
[0016] As a preferred embodiment, the conditions for silver removal by dissolution are: a liquid-to-solid mass ratio of (7~9):1, a dissolution time of 20~40 min, and a temperature of 25~45℃. Furthermore, by controlling the silver removal by dissolution within the selected range, this invention facilitates achieving a high silver leaching rate under mild conditions while avoiding silver re-plating.
[0017] As a preferred embodiment, the silver-containing leachate is subjected to reduction treatment and / or electrolytic deposition treatment to obtain silver powder.
[0018] As a preferred embodiment, the silicon / aluminum mass ratio of the silicon-aluminum composite solid phase and the raw materials including metallic aluminum is (0.12~0.135):1. Within the Si / Al mass ratio range selected in this invention, it is beneficial to ensure good melt flowability and die-casting performance of the alloy, while avoiding brittle cracking of the alloy due to coarse primary silicon crystals, and promoting sufficient mutual solubility and homogeneity of the silicon and aluminum phases, reducing component segregation and melting defects.
[0019] As a preferred embodiment, the smelting process includes two stages: low-temperature pre-melting and high-temperature smelting. This invention first melts the metallic aluminum phase within the system through low-temperature pre-melting, allowing the molten aluminum to wet and encapsulate the silicon particles in the silicon-aluminum composite solid phase. This breaks down the oxide film on the silicon surface, activates the solid-liquid interface, and prevents silicon agglomeration and sedimentation, as well as subsequent component segregation. Then, high-temperature smelting with slow heating and tempering achieves uniform solid solution of silicon, avoiding defects such as coarse primary silicon crystals, porosity, and inclusions. This significantly improves the compositional stability and finished product yield of the ADC12 aluminum alloy ingot.
[0020] As a preferred embodiment, the low-temperature pre-melting temperature is 580~620℃, the heating rate is 8~10℃ / min, and the holding time is 20~40min. Experiments have shown that the temperature and time range of the low-temperature pre-melting of this invention can produce only a small amount of aluminum-silicon eutectic liquid phase, mainly for wetting and activating the oxide film. The vast majority of silicon remains dispersed in the aluminum liquid phase as solid particles, preventing a large-scale dissolution at once and fundamentally avoiding localized silicon over-limitation. Excessive temperature leads to excessive fluidity of the aluminum liquid, causing unencapsulated fine silicon particles to float or sink directly, resulting in stratification and segregation. Furthermore, excessively rapid heating at this stage causes a sudden rise in furnace temperature, with the outer aluminum layer melting quickly while the interior of the material remains in a low-temperature solid state. This extreme temperature difference causes the silicon surface to oxidize instantaneously at high temperature, forming a dense SiO2 oxide shell that hinders aluminum penetration. The silicon, encapsulated by the oxide film, is difficult to dissolve into the aluminum matrix, resulting in inclusions of silicon particles and hard spots.
[0021] As a preferred embodiment, the high-temperature melting temperature is 720~760℃, and the heating rate is 3~5℃ / min. The purpose of the high-temperature melting in this invention is to slowly heat the aluminum molten metal to allow solid silicon particles to dissolve evenly and uniformly, completing alloying and tempering. This is then combined with degassing and slag removal refining to control the melt composition and impurities within the acceptable ADC12 range. If the temperature is too low at this stage, the solubility of silicon in the aluminum molten metal is insufficient, and some silicon particles cannot be completely dissolved in the melt, resulting in poor melt fluidity. If the temperature is too high, the melt will overheat, and the mechanical properties of the alloy will decrease. In addition, controlling the heating rate at the high-temperature stage is also very important. If the heating rate is too fast, a large amount of silicon particles will dissolve rapidly in a short time, causing the silicon concentration in local areas to exceed the standard instantaneously, making the alloy brittle and prone to cracking during die casting. If the heating rate is too slow, the melt will remain in the medium-high temperature range for a long time, increasing the aluminum burn-off.
[0022] In practice, during the high-temperature smelting stage, the alloy composition can be adjusted according to the requirements of the ADC12 aluminum alloy composition.
[0023] As a preferred embodiment, the smelting process further includes stirring and homogenizing, degassing, and slag removal refining. The stirring and homogenizing, degassing, and slag removal refining processes used in this invention are conventional steps in the aluminum alloy preparation process.
[0024] Compared with the prior art, the present invention has at least the following beneficial effects:
[0025] (1) The method of the present invention uses failed photovoltaic silicon wafers generated during the recycling process in the photovoltaic industry as raw materials, forms a protective film through a pre-passivation liquid, and then selectively dissolves the silver grid with a silver-containing leaching solution to completely retain the aluminum back field, thereby obtaining a silicon-aluminum composite raw material that can directly replace high-purity silicon for the preparation of ADC12 alloy, realizing efficient resource utilization and low-cost recycling of failed photovoltaic silicon wafers.
[0026] (2) This invention not only realizes the resource utilization of photovoltaic waste, but also reduces the production cost of ADC12 aluminum alloy. It is simple to operate, has low production cost, and has good environmental, economic and social benefits.
[0027] (3) The pre-passivation process of the present invention solves the problem of passivation failure of the edges and corners of the crushed material. The slow-release passivation silver immersion solution used can be reused, reducing the consumption of the agent, reducing the amount of hazardous waste generated, and is free of thiourea, which is highly toxic, and the wastewater treatment is easy.
[0028] (4) This invention proposes a process for preparing ADC12 aluminum alloy using silicon-aluminum composite raw materials obtained from failed photovoltaic silicon wafers. The two-stage melting process of low-temperature pre-melting and high-temperature melting effectively solves the problems of uneven composition and numerous defects in traditional waste melting. Low-temperature pre-melting can activate and wet the silicon-aluminum interface, preventing silicon particle agglomeration and segregation. High-temperature melting can achieve uniform solid solution of silicon, eliminating defects such as coarse primary silicon, pores, and inclusions, and significantly improving the compositional stability and finished product qualification rate of ADC12 aluminum alloy ingots. The prepared ADC12 aluminum alloy has excellent comprehensive mechanical properties and low slag content. Attached Figure Description
[0029] Figure 1 This is a process flow diagram of a method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy according to the present invention.
[0030] Figure 2 This is a process flow diagram of the two-stage melting process for preparing ADC12 aluminum alloy ingots according to the present invention. Detailed Implementation
[0031] The following examples are intended to further illustrate the present invention, but not to limit the scope of protection of the claims of the present invention.
[0032] To further illustrate the method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy according to the present invention, and to achieve the intended purpose of the invention, the following, in conjunction with preferred embodiments, provides a detailed description of the specific implementation, structure, features, and effects of the method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers according to the present invention. In the following description, different "an embodiment" or "an embodiment" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics in one or more embodiments may be combined in any form.
[0033] The following will describe specific embodiments in conjunction with... Figure 1 and Figure 2 The flowchart below provides a more detailed description of the method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy according to the present invention:
[0034] In the embodiments and comparative examples of this invention, the ADC12 aluminum alloy, by mass percentage, comprises: silicon (Si) 9.6%–12.0%, copper (Cu) 1.5%–3.5%, iron (Fe) ≤1.3%, zinc (Zn) ≤1.0%, magnesium (Mg) ≤0.3%, manganese (Mn) ≤0.5%, nickel (Ni) ≤0.5%, tin (Sn) ≤0.3%, lead (Pb) ≤0.3%, with the balance being Al.
[0035] Example 1
[0036] Using degraded photovoltaic silicon wafers from a certain factory as raw materials (silicon content 93.20wt%, silver content 0.88wt%, metallic aluminum content 5.10wt%, other impurities 0.82wt%), the raw materials were crushed, sieved, ultrasonically washed, and dried. The dried raw materials were then placed in a 0.5wt% tartaric acid pre-passivation aqueous solution. The silicon wafer fragments were soaked in the solution at room temperature (25℃) for 2 minutes and then quickly rinsed with water. They were then placed in an anti-corrosion silver immersion solution. The anti-corrosion silver immersion solution consisted of the following components by mass percentage: 4.5% nitric acid (the nitric acid was diluted with water using 65wt% industrial concentrated nitric acid, and HNO3 accounted for 4.5% of the total solution mass in the entire slow-release silver immersion mixed solution system), 1.0% tartaric acid, 0.5% thiomalic acid, 0.2% ammonium nitrate, 0.15% fatty alcohol polyoxyethylene ether, and the balance being deionized water. The liquid-to-solid mass ratio for silver removal was controlled at 8:1, the stirring leaching time was 30 min, and the system temperature was 35℃. After the silver removal was completed, solid-liquid separation was performed to obtain a silver-containing leachate and a silicon-aluminum composite solid phase (referred to as silver-removed silicon-aluminum composite material).
[0037] The silver-containing leaching solution and the desilvered silicon-aluminum composite were tested. The leaching rate of Ag was 99.43%, the removal rate of other impurities was 90.12%, and the Al loss rate was 0.39%. The Ag leaching rate, Al loss rate, and removal rate of other impurities all met the standards, and the desilvered silicon-aluminum composite can be directly used as a raw material for preparing ADC12 aluminum alloy. The silver-containing leaching solution can be further processed by electrolytic deposition to obtain silver powder.
[0038] The raw materials of the above-mentioned ADC12 aluminum alloy (silicon content 94.75wt%, metallic aluminum content 5.16wt%, other impurities 0.09wt%) are mixed with metallic aluminum to make the Si / Al mass ratio 0.125, and metallic copper is added to make the copper content 2.0wt%. The mixed raw materials are sent to a melting furnace, first heated to 600℃ at a heating rate of 9℃ / min and held for 30min, and then heated to 740℃ at a heating rate of 4℃ / min. The alloy composition is adjusted according to the requirements of ADC12 aluminum alloy. After stirring, homogenization, degassing, slag removal and refining, qualified ADC12 aluminum alloy melt is obtained, which is then cast into ADC12 aluminum alloy ingots.
[0039] The product was tested and found to have a tensile strength of 242 MPa, a yield strength of 165 MPa, and an elongation after fracture of 1.72%, which meets the product quality standards. The slag content is 8.14%, which allows for industrial application.
[0040] Example 2
[0041] Using degraded photovoltaic silicon wafers (93.20 wt% silicon, 0.88 wt% silver, 5.10 wt% aluminum, and 0.82 wt% other impurities) from a certain factory as raw material, the raw material was crushed, sieved, ultrasonically washed, and dried. The dried raw material was then immersed in a 0.4 wt% tartaric acid pre-passivation aqueous solution at 25°C for 3 minutes, followed by rapid rinsing with water. It was then placed in an anti-corrosion silver leaching solution, which, by mass percentage, consisted of: 4.5% dilute nitric acid, 1.5% tartaric acid, 0.3% thiomalic acid, 0.15% ammonium nitrate, 0.2% fatty alcohol polyoxyethylene ether, with the balance being deionized water. The silver removal process was controlled with a liquid-to-solid mass ratio of 8:1, a stirring leaching time of 30 minutes, and a system temperature of 45°C. After silver removal, solid-liquid separation was performed to obtain a silver-containing leachate and a silicon-aluminum composite solid phase (referred to as the desilvered silicon-aluminum composite material).
[0042] The leachate and the desilvered silicon-aluminum composite were tested, and the Ag leaching rate was 99.09%, the removal rate of other impurities was 91.10%, and the Al loss rate was 0.63%. The Ag leaching rate, Al loss rate, and removal rate of other impurities all met the standards, and the desilvered silicon-aluminum composite can be directly used as a raw material for preparing ADC12 aluminum alloy.
[0043] The above-mentioned desilvered silicon-aluminum composite material (silicon content 94.76wt%, metallic aluminum content 5.15wt%, other impurities 0.08wt%) was used as the raw material for ADC12 aluminum alloy. It was mixed with metallic aluminum to make the Si / Al mass ratio 0.125, and metallic copper was added to make the copper content 2.0wt%. The mixed raw material was sent to a melting furnace. It was first heated to 600℃ at a heating rate of 9℃ / min and held for 40min. Then it was heated to 740℃ at a heating rate of 4℃ / min and the alloy composition was adjusted according to the requirements of ADC12 aluminum alloy. After stirring, homogenization, degassing, slag removal and refining, qualified ADC12 aluminum alloy melt was obtained. It was then cast into ADC12 aluminum alloy ingots.
[0044] The product was tested and found to have a tensile strength of 243 MPa, a yield strength of 159 MPa, and an elongation after fracture of 1.65%, which meets the product quality standards. The slag content is 8.45%, which allows for industrial application.
[0045] Example 3
[0046] The only difference between this embodiment and Embodiment 1 is that the temperature for dissolving and removing silver is adjusted to 50°C. All other steps and conditions are the same. After the silver is dissolved and removed, solid-liquid separation is performed to obtain a silver-containing leachate and a composite solid phase containing silicon and aluminum (referred to as desilvered silicon-aluminum composite material).
[0047] The leachate and the desilvered silicon-aluminum composite were tested. The Ag leaching rate was 96.02%, the removal rate of other impurities was 88.54%, and the Al loss rate was 19.02%. The Ag leaching rate decreased, while the Al loss rate increased significantly.
[0048] Example 4
[0049] The only difference between this embodiment and Embodiment 1 is that the liquid-solid mass ratio for dissolving and removing silver is changed to 5:1. All other steps and conditions are the same. After the silver is dissolved and removed, solid-liquid separation is performed to obtain a silver-containing leachate and a silicon-aluminum composite solid phase (referred to as desilvered silicon-aluminum composite material).
[0050] The leachate and the silver-free silicon-aluminum composite were tested, and the Ag leaching rate was 98.07%, the removal rate of other impurities was 86.95%, and the Al loss rate was 4.51%. 3+ Ag + Localized oversaturation resulted in slight precipitation and silver back-plating, leading to a decrease in both Al loss rate and Ag leaching rate.
[0051] Example 5
[0052] The only difference between this embodiment and Example 1 is that the concentration of the tartaric acid prepassivation aqueous solution is adjusted to 2wt%; the other steps and conditions are the same. After the silver is dissolved and removed, solid-liquid separation is performed to obtain a silver-containing leachate and a silicon-aluminum composite solid phase (referred to as desilvered silicon-aluminum composite material).
[0053] The leachate and the silver-free silicon-aluminum composite were tested, and the Ag leaching rate was 95.57%, the removal rate of other impurities was 86.71%, and the Al loss rate was 5.29%.
[0054] Example 6
[0055] The silver-free silicon-aluminum composite material prepared in Example 1 was used as the raw material for preparing ADC12 aluminum alloy (silicon content 94.75wt%, metallic aluminum content 5.16wt%, other impurities 0.09wt%). It was mixed with metallic aluminum to make the Si / Al mass ratio 0.125, and metallic copper was added to make the copper content 2.0wt%. The mixed raw material was sent to a melting furnace, heated to 620℃ at a heating rate of 10℃ / min and held for 30min. Then it was heated to 750℃ at a heating rate of 4℃ / min and the alloy composition was adjusted according to the requirements of ADC12 aluminum alloy. After stirring, homogenization, degassing, slag removal and refining, qualified ADC12 aluminum alloy melt was obtained, which was then cast into ADC12 aluminum alloy ingots.
[0056] The product was tested and found to have a tensile strength of 244 MPa, a yield strength of 159 MPa, and an elongation after fracture of 1.68%, which meets the product quality standards. The slag content is 8.49%, which allows for industrial application.
[0057] Example 7
[0058] The silver-free silicon-aluminum composite material prepared in Example 1 was used as the raw material for preparing ADC12 aluminum alloy (silicon content 94.75wt%, metallic aluminum content 5.16wt%, other impurities 0.09wt%). It was mixed with metallic aluminum to make the Si / Al mass ratio 0.125. The mixed raw material was sent to the melting furnace and heated to 600℃ at a heating rate of 9℃ / min and held for 40min. Then, it was heated to 720℃ at a heating rate of 4℃ / min and the alloy composition was adjusted. After stirring, homogenization, degassing, slag removal and refining, qualified ADC12 aluminum alloy melt was obtained and cast into ADC12 aluminum alloy ingot.
[0059] The product was tested and found to have a tensile strength of 241 MPa, a yield strength of 157 MPa, and an elongation after fracture of 1.61%, which meets the product quality standards. The slag content is 8.52%, which allows for industrial application.
[0060] Example 8
[0061] The only difference between this embodiment and Embodiment 1 is that low-temperature pre-melting is not performed. Instead, the temperature is directly increased to 740°C at a heating rate of 4°C / min, and the alloy composition is adjusted. All other steps and conditions are the same, resulting in ADC12 aluminum alloy ingots.
[0062] The tensile strength was 184 MPa, the yield strength was 110 MPa, and the elongation after fracture was 0.86%.
[0063] Example 9
[0064] The only difference between this embodiment and Embodiment 1 is that the temperature is first raised to 550°C at a heating rate of 9°C / min and held for 30 minutes, and then raised to 740°C at a heating rate of 4°C / min while adjusting the alloy composition. All other steps and conditions are the same, resulting in ADC12 aluminum alloy ingots.
[0065] The tensile strength was tested to be 186 MPa, the yield strength to be 113 MPa, and the elongation after fracture to be 0.88%.
[0066] Example 10
[0067] The only difference between this embodiment and Embodiment 1 is that the temperature is first raised to 650°C at a heating rate of 9°C / min and held for 30 minutes, and then raised to 740°C at a heating rate of 4°C / min while adjusting the alloy composition. All other steps and conditions are the same, resulting in ADC12 aluminum alloy ingots.
[0068] The product was tested and found to have a tensile strength of 234 MPa, a yield strength of 158 MPa, and an elongation after fracture of 1.61%, which is considered qualified. However, the Si content was 9.83%, which is slightly below the lower limit, and the amount of slag increased during the smelting process.
[0069] Comparative Example 1
[0070] Using degraded photovoltaic silicon wafers sorted from a certain factory as raw materials (silicon content 93.20wt%, silver content 0.88wt%, metallic aluminum content 5.10wt%, other impurities 0.82wt%), the raw materials were crushed, screened, washed, and dried. The dried raw materials were then placed in deionized water, with the liquid-to-solid mass ratio controlled at 8:1, the stirring and leaching time at 30 min, and the system temperature at 35℃.
[0071] The leachate and the silver-free silicon-aluminum composite were tested. The Ag leaching rate was 76.14%, the removal rate of other impurities was 57.32%, and the Al loss rate was 0.59%. The Ag leaching rate and the removal rate of other impurities did not meet the standards, and there were many impurities remaining and the Ag leaching rate was low.
[0072] Comparative Example 2
[0073] The only difference between this comparative example and Example 1 is that no pre-passivation treatment is performed. All other steps and conditions are the same. After the silver is dissolved and removed, solid-liquid separation is performed to obtain a silver-containing leachate and a silicon-aluminum composite solid phase (referred to as desilvered silicon-aluminum composite material).
[0074] The leachate and the silver-free silicon-aluminum composite were tested. The Ag leaching rate was 93.18%, the removal rate of other impurities was 70.73%, and the Al loss rate was 17.25%. The Ag leaching rate did not meet the standard, and the Al loss rate was too high.
[0075] Comparative Example 3
[0076] The only difference between this comparative example and Example 1 is that the silver leaching solution is replaced with a 10wt% dilute nitric acid solution. All other steps and conditions are the same. After the silver is dissolved and removed, solid-liquid separation is performed to obtain a silver-containing leachate and a silicon-aluminum composite solid phase (referred to as desilvered silicon-aluminum composite material).
[0077] The leachate and the desilvered silicon-aluminum composite were tested. The Ag leaching rate was 99.09%, the removal rate of other impurities was 86.59%, and the Al loss rate was 26.27%. The Ag leaching rate and the removal rate of other impurities met the standards, but the Al loss rate increased significantly.
Claims
1. A method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy, characterized in that: After the failed photovoltaic silicon wafers are crushed and screened, they are immersed in a pre-passivation solution to form a passivation film, and then dissolved to remove silver. After solid-liquid separation, a silver-containing leachate and a silicon-aluminum composite solid phase are obtained. The silicon-aluminum composite solid phase is smelted and cast into ADC12 aluminum alloy by adding raw materials including metallic aluminum according to the composition of ADC12 aluminum alloy.
2. The method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy according to claim 1, characterized in that: The crushing and screening process controls the particle size to be 2-20 mm; the crushing and screening process also includes a washing process. The failed photovoltaic silicon wafer mainly contains 92~94wt% Si, 0.6~1.0wt% Ag, and 4~6wt% Al.
3. The method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy according to claim 1, characterized in that: The pre-passivation solution is a 0.4~0.6wt% tartaric acid aqueous solution, and the soaking time is 1~3 min.
4. A method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy according to any one of claims 1 to 3, characterized in that: The silver removal process employs an anti-corrosion silver immersion solution, which, by mass percentage, comprises the following components: 3-6% nitric acid, 0.8-1.5% tartaric acid, 0.3-0.6% thiomalic acid, 0.15-0.25% ammonium nitrate, 0.1-0.2% fatty alcohol polyoxyethylene ether, with the balance being water.
5. The method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy according to claim 4, characterized in that: The conditions for dissolving and removing silver are: a liquid-to-solid mass ratio of (7~9):1, a dissolution time of 20~40 min, and a temperature of 25~45℃.
6. The method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy according to claim 1, characterized in that: The silver-containing leachate is subjected to reduction treatment and / or electrolytic deposition treatment to obtain silver powder.
7. A method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy according to claim 1 or 6, characterized in that: The silicon-aluminum composite solid phase and the raw materials including metallic aluminum are mixed in a silicon / aluminum mass ratio of (0.12~0.135):
1.
8. The method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy according to claim 7, characterized in that: The smelting process includes two stages: low-temperature pre-melting and high-temperature smelting.
9. The method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy according to claim 8, characterized in that: The temperature of the low-temperature pre-melting is 580~620℃, the heating rate is 8~10℃ / min, and the holding time is 20~40min; and / or; The high-temperature melting temperature is 720~760℃, and the heating rate is 3~5℃ / min.
10. The method for selectively removing silver and preserving aluminum from failed photovoltaic silicon wafers to prepare ADC12 aluminum alloy according to claim 1, characterized in that: The process after smelting also includes stirring and homogenization, degassing, and slag removal refining.